Characterizations of Simple Points on the Body-Centered Cubic Grid - Kardos, Péter (Combinatorial Image Analysis, 2020)
A frequently investigated problem in various applications of binary image processing is to ensure the topology preservation of image operators, where the concept of simple points plays a key role. The literature primarily focuses on 2D and 3D images that are sampled on the conventional square and cubic grids, respectively. This paper presents some new characterizations of simple points on the body-centered cubic grid.